Carotid intima-media thickness and plaques in internal carotid artery as surrogate markers of lower limb arterial lesions in Chinese patients with diabetic foot - Mei Zhang; Xiaorong Wen; Chenyun Zhou; Jing Huang; Ying He (Brazilian Journal of Medical and Biological Research)
Peripheral arterial disease (PAD) can impair healing of diabetic foot (DF) in patients with diabetes mellitus. To determine whether carotid intima-media thickness (CIMT) can predict lower limb arterial lesions in patients with DF, this cross-sectional study enrolled patients with DF at West China Hospital (China) between January 2012 and December 2015. Ultrasonography was used to measure CIMT, assess the internal carotid arteries (ICA) for plaques, and evaluate lower limb segmental arteries for stenosis. The optimal CIMT cutoff for detecting lower limb PAD was determined by receiver operating characteristic (ROC) curve analysis. Factors associated with PAD were identified by logistic regression analyses. A total of 167 patients (mean age: 69.7±10.3 years; 102 men) were included. Patients with PAD were older and had higher levels of total cholesterol and low-density lipoprotein than patients without PAD (P<0.05). The area under the ROC curve was 0.747 (P<0.001). At the optimal CIMT cutoff of 0.71 mm, the sensitivity, specificity, positive predictive value, and negative predictive value were 79.65, 61.11, 81.08, and 58.93%, respectively. Compared with those without PAD, more patients with PAD had CIMT ≥0.71 mm (79.65 vs 38.89%; P<0.001) and ICA plaques (66.37vs 11.11%; P<0.001). Multivariate logistic regression revealed that age (odds ratio [OR]: 1.118; 95% confidence interval [95%CI]: 1.056–1.183; P<0.001), ICA plaques (OR: 13.452; 95%CI: 4.450–40.662; P<0.001), and CIMT ≥0.71 mm (OR: 2.802; 95%CI: 1.092–7.188; P=0.032) were associated with PAD.CIMT may be a surrogate marker of PAD in patients with DF.